Pengembangan Sistem Informasi Pengelolaan Klinik Gigi Berbasis Website Menggunakan Prinsip Point of Sale (Studi Kasus: Klinik Gigi Senyum Sehat Dental Care) - Rafiqah Majidah; Denny Sagita Rusdianto; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Senyum Sehat Dental Care is a dental clinic which has been operating for 3 years. The number of patients recorded by the dental clinic is numbered approximately at 500. Along with the development and the increasing number of patients of this dental clinic, various problems arise, one of the problems that arise is lack of work efficiency in terms of time and exerted effort. The next problem is lack of information on the amount of dental care ingredients availability. Based on these problems, it is necessary to develop an efficient system to assist the dental clinic to better save time and exerted efforts. In order to test whether the system that has been developed is correct according to the needs, unit, integration, and validation testing with white-box and black-box method used in this case. Non functional testing takes efficiency aspects by testing the system performance to see the load time, then comparing the time needed before and after using the system. The results of validation, unit, integration, and performance testing are 100% valid. This system can increase time efficiency 30 times faster than before using the system.